Travel across time zones and the implications for human performance post pandemic: Insights from elite sport - Jasper, Stephen C.; Leenders, Mark A. A. M.; O'Shannassy, Tim (Frontiers in Public Health, 2022)
Notwithstanding technological innovation, the COVID-19 pandemic, and new communication tools, the need for travel is growing again and, in some travel segments, it is stronger than ever. Interestingly, the public health implications of travelling across time zones are still poorly understood and this is especially true for organizations that send their workers across the globe. Using data from 173 Olympic teams over 15 Olympic Games, we show that crossing multiple time zones has negative implications for human (sports) performance. More importantly, the results indicate that performance impairment is especially visible after flying east, with peak performance particularly impaired, leading to a “gold demotion effect” of gold medals to silver medals as a result. Given that Olympic sporting teams typically have dedicated medical staff and active mitigation strategies, these findings have important public health implications. For example, organizations are demanding their workers to be on ‘top of their game’ while travelling, without providing them with the support and tools to do so. The implications for public health management and human resource management are discussed.